The Numerical Representation of Ordered Classifications and the Concept of Utility - Samuelson, Paul A. (Review of Economic Studies, 1938)
Journal Article The Numerical Representation of Ordered Classifications and the Concept of Utility Get access Paul A. Samuelson Paul A. Samuelson Cambridge, Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 65–70, https://doi.org/10.2307/2967540 Published: 01 October 1938